P–371 Clinical value assessment between endometrial receptivity array and immune profiling in patients with implantation failure. (6th August 2021) - Dong, Y; Jia, Y; Sha, Y; Diao, L; Cai, S; Qiu, Z; Guo, Y; Tan, A; Huang, Y; Zhong, Y; Ye, H; Liu, S
Abstract: Study question: To evaluate whether the pregnancy outcomes could be improved in implantation failure patients by endometrial receptivity array, endometrial immune profiling, or a combination of both. Summary answer: There was no statistical difference between different endometrial receptivity evaluation and treatment in improving the clinical pregnancy rate. What is known already: Both endometrial receptivity array and endometrial immune profiling were promised to improve the endometrial receptivity and subsequent clinical pregnancy. However, less is known about the efficiency between each other and whether the combination could further enhance their clinical value. Study design, size, duration: Between November 2019 and September 2020, 143 women with a history of at least two or more consecutive implantation failure in IVF/ICSI treatment in Chengdu Xinan Gynecology Hospital were included. They were divided into three groups: 'ERA + Immune Profiling' (n = 70), 'Immune Profiling' (n = 41), and 'ERA' (n = 32). Participants/materials, setting, methods: Inclusion criteria were age ≤ 38, with normal uterus and uterine cavity. All patients were suggested to evaluate endometrial receptivity by ERA test (Igenomix, Valencia, Spain) and endometrial immune profiling based on immunohistochemistry simultaneously, who would be free to choose each or both evaluation approaches. Personal Embryo Transfer and/or personal medical care were adopted according to evaluation results. Clinical pregnancy was confirmed by gestational sacs observed under ultrasonography. Main results and the role of chance: The overall prevalence of displaced window of implantation (WOI) is 84.3%, and nearly 74.8% (83/111) patients were diagnosed as endometrial immune dysregulation. Clinical Pregnancy rate and embryonic implantation rate decreased in the 'Immune Test' groups, but without a statistical difference (P = 0.311, and 0.158, respectively). Multivariable logistic regression analysis showed that different endometrial receptivity evaluation and treatment was not associated the clinical pregnancy rate, suggesting the performance of different endometrial receptivity evaluation and treatment is similar in improving the clinical pregnancy rate. Neither the immune profiling (CD56, P = 0.591; FOXP3, P = 0.195; CD68, P = 0.820; CD163, P = 0.926; CD1a, P = 0.561; CD57, P = 0.221; CD8, P = 0.427; CD138 CE, P = 0.372) nor histologic endometrial dating defined by Noyes criteria (P = 0.374) were associated with ERA phases. Limitations, reasons for caution: Although the selection of evaluation approaches was based on patients' willingness, the variances of baseline characteristics and immune profiling existed in different groups. The immunological treatment efficacy based on immune profiling was not evaluated before embryo transfer. Wider implications of the findings: To our knowledge, this is the first study comparing the pregnancy outcomes after two typical endometrial receptivity evaluation approaches. The findings highlight the unsubstitutability for each assessment, indicating that both asynchronous and pathological WOI contribute to implantation failure. Trial registration number: X2019004